Biodegradable poly(lactide-co-glycolide) microspheres encapsulating hydrophobic contrast agents for transarterial chemoembolization - Jeon, Seong Ik; Kim, Moo Song; Kim, Hyung Jun; Kim, Young Il; Jae, Hwan Jun; Ahn, Cheol-Hee (Journal of biomaterials science. Polymer ed., 2022)
Transarterial chemoembolization (TACE) is a therapeutic approach to address hepatocellular carcinoma by obstructing the blood supply to the tumor using embolic agents and improving the local delivery of anticancer agents. Size-calibrated polymeric microspheres (MSs) termed drug-eluting beads (DEBs) are the most prevalent solid embolic materials; however, their limitations include insufficient X-ray visibility or biodegradability. In this study, size-controlled polymeric MSs with inherent radiopacity and biodegradability were created, and their embolic effect was assessed. Poly(lactide-co-glycolide) MSs (PLGA MSs) incorporating a hydrophobic X-ray contrast agent and an anticancer drug were produced by the w/o/w emulsion process. Their sizes were exactly calibrated to 71.40 ± 32.18 and 142.66 ± 59.92 μm in diameter, respectively, which were confirmed to have sizes similar to the clinically available DEBs. The iodine content of PLGA MSs was calculated as 144 mgI/g, and the loading quantity of the drug was 1.33%. Manufactured PLGA MSs were gradually degraded for 10 weeks and consistently released the anticancer drug. Following the PLGA MSs injection into the renal artery of New Zealand white rabbit test subjects, their deliverability to the targeted vessel through the microcatheter was confirmed. Injected PLGA MSs were clearly imaged through the real-time X-ray device without blending any contrast agents. The embolic effect of the PLGA MSs was ultimately established by the atrophy of an embolized kidney after 8 weeks. Consequently, the designed PLGA MS is anticipated to be an encouraging prospect to address hepatocellular carcinoma.